Subcutaneous Interferon β-1a Administration by Electronic Auto-injector is Associated with High Adherence in Patients with Relapsing Remitting Multiple Sclerosis in a Real-life Study - Järvinen, Elina (Neurol Int, 2017)
The objective was to investigate adherence measured by an electronic auto-injector device, and self-reported adherence and treatment convenience in subjects with relapsing remitting multiple sclerosis (RRMS), using an electronic auto-injector Rebismart(®) to self-inject interferon β-1a. Thirty one patients with RRMS using the electronic auto-injector Rebismart(®) for self-injecting interferon β-1a subcutaneously three times weekly were included in a real-life clinical multicenter study for 24 weeks in Finland. Mean adherence reported by the device and mean self-assessment of adherence were studied. Reasons for missing injections and treatment convenience were assessed. Association between adherence and gender and age were studied. The mean adherence calculated from the device data was 93.5%. The mean self-assessment of adherence was 96.6%. The most common reason for missing an injection was forget-fulness. Adherence (measured by the device) was not changed over time. In the high adherence group there were more females and young patients (<30 years of age). The auto-injector was found to substantially ease the treatment by 90% of the patients. The electronic auto-injector was associated with high adherence to treatment. The device was found to ease the patient’s treatment and it was perceived as easy to use. It is a convenient tool to assess patient’s adherence to treatment.